2002
DOI: 10.1097/00000539-200207000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Serum Creatinine Patterns in Coronary Bypass Surgery Patients With and Without Postoperative Cognitive Dysfunction

Abstract: We previously noted that patients with postcardiac surgery stroke also have greater acute renal injury than unaffected patients. However, in the same setting, we found no difference in renal injury between patients with and without cognitive dysfunction. Factors responsible for subtle postoperative cognitive dysfunction do not appear to be associated with clinically important renal effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Interestingly, another study, evaluating 282 patients, specifically examined the relationship between serum creatinine and postoperative cognitive decline and was unable to establish an association. 18 This discordance may be caused by a lack of power, misspecification of the covariates, or the different time frame of neurocognitive testing. In our cohort, preoperative serum creatinine was a strong predictor of cognitive decline and demonstrated a threshold relationship with the risk of POCDs with sharp increases in the odds of POCDs at creatinine levels Ͼ125 mmol/L.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, another study, evaluating 282 patients, specifically examined the relationship between serum creatinine and postoperative cognitive decline and was unable to establish an association. 18 This discordance may be caused by a lack of power, misspecification of the covariates, or the different time frame of neurocognitive testing. In our cohort, preoperative serum creatinine was a strong predictor of cognitive decline and demonstrated a threshold relationship with the risk of POCDs with sharp increases in the odds of POCDs at creatinine levels Ͼ125 mmol/L.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Bhatraju et al 2 study additionally highlights the shortfall of current AKI staging criteria used alone in assessing outcomes, as the severity stage by itself did not differentiate among which patients would develop MAKE; rather, the recovery pattern was more informative. This finding was similarly seen in the coronary artery bypass graft3 and intensive care unit 4 cohort studies and in aggregate emphasizes the need for clinicians to consider the patient's course after AKI as a determinant of outcome.Although there is now increasing interest in understanding the timing of recovery to identify distinct phenotypes prone to adverse outcomes, it is important to realize that these are just initial pieces of the puzzle. For instance, the ability to distinguish recovery from nonrecovery and the timing thereof depends on the definitions used.…”
mentioning
confidence: 59%
“…The study by Bhatraju et al 2 study additionally highlights the shortfall of current AKI staging criteria used alone in assessing outcomes, as the severity stage by itself did not differentiate among which patients would develop MAKE; rather, the recovery pattern was more informative. This finding was similarly seen in the coronary artery bypass graft 3 and intensive care unit 4 cohort studies and in aggregate emphasizes the need for clinicians to consider the patient's course after AKI as a determinant of outcome.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Serum creatinine (Cre) has emerged as an indicator of renal function and has garnered considerable research interest as a predictor of various medical conditions, including diabetes, cardiovascular disease, pregnancy, and obesity [13][14][15][16][17][18]. Consequently, the investigation into the association between serum Cre and cognitive function has gained momentum [19][20][21][22][23][24]. One study reported no statistically signi cant link between lower Cre clearance and cognitive impairment [24].…”
Section: Introductionmentioning
confidence: 99%